Dying T cells trigger autoimmunity in HIV. - Rowland-Jones, S; Dong, T (2007)
During HIV-1 infection, there are many ways for CD4+ T cells to die. New findings suggest that an autoimmune mechanism may come into play (pages 1431-1439). © 2007 Nature Publishing Group.